Strategic Integration of MICE Tourism for Enhancing Sharia Hotel Occupancy in Medan City - Muhammad Arif Fadhillah Lubis; Muhammad Syukri Albani Nasution; Fauzi Arif Lubis (Journal of Islamic Economics and Business, 2025)
This study investigates how Sharia hotels in Medan, Indonesia, can optimize MICE (Meetings, Incentives, Conventions, and Exhibitions) tourism to increase occupancy rates. The issue arises from overreliance on government-related events and recent budget reductions, which have weakened performance and underscored the need for alternative marketing strategies. This research contributes novelty by proposing an integrative model that blends digital marketing, collaborative partnerships, and Islamic service values, which remain underexplored in hospitality studies. Employing a qualitative approach through interviews and secondary data, the study identifies five strategic directions: market diversification, enhancement of digital and hybrid meeting technologies, development of a collaborative MICE ecosystem, inclusive marketing education, and pursuit of regulatory support. The analysis is grounded in Social Identity Theory and the Resource-Based View, demonstrating how a strong Islamic service identity and effective resource utilization can strengthen competitiveness. Findings suggest that a holistic and adaptive integration of MICE tourism not only boosts occupancy but also expands customer segments while preserving Sharia compliance. The study concludes that moving beyond a government-centric model toward a diversified, digitally driven strategy is essential for the long-term sustainability of Sharia hotels in Indonesia.